A Novel Technique of Controlling Signal Propagation within Array Elements using Switchable Miniaturized Electromagnetic Band Gap - Mohamad Isa, Mohd Sa'ari; Awang Md Isa, Azmi; Mohd Zin, Mohd Shahril Izuan; Zakaria, Zahriladha; Haron, Nor Zaidi; Asmala, A. (IEEE, 2013)
In this paper, a novel miniaturized capacitive loaded electromagnetic band gap (EBG) has been developed with the patch size of approximately !/36. The dimension is controllable using the lumped capacitive elements values. The surface impedance characteristic of the EBG structure is switchable as pin vias have been inserted and removed within the EBG center and the ground plane. Switching the EBG surface impedance characteristic within the array elements has demonstrated the novel application of miniaturized EBG to control the signal propagation within the array elements. Radiation pattern for the middle antenna is enhanced toward the antenna which connected with low surface impedance EBG structure resulting approximately 12dB improvement in gain. The propagation characteristics and gain of the array have been analyzed using CST Microwave Studio (CST MWS). The new application of the EBG can be very useful to realize the controlling and channeling the signal within the array elements.